Measuring Market Power in German Food Retailing : regional evidence - Anders, Sven; Justus Liebig University Giessen (My University, 2005)
Due to increasing concentration and a rapidly changing competitive environment in many food markets, it can be expected that farmers and processors suffer from the exertion of retail market power. This might the case in particular on those regional markets where small-scaled marketing structures dominate. Given this background, it is he aim of this paper to explicitly analyse the simultaneous exertion of retailers´ market power in the regional output and input markets of a segment of the German meat market. Based on the production-theory approach proposed by Gohin and Guyomard (2000) the model parameterizes the retail industry´s oligopoly and oligopsony equilibria. Standard market power measures like Lerner indexes are computed and selected elasticities of factor supply and industry demand are provided. Results suggest that the hypothesis of perfect competition and price-taking behaviour clearly has to be rejected. However, estimates of conjectural elasticities indicate retailers´ upstream and downstream market power in regional meat marketing is limited.
Keywords: food retailing; meat marketing; oligopoly; oligopsony; conjectural variation; ddc:630